Review—Two-Dimensional Boron Carbon Nitride: A Comprehensive Review. (25th September 2020) - Angizi, Shayan; Akbar, Md Ali; Darestani-Farahani, Maryam; Kruse, Peter
Abstract : Two-dimensional Boron Carbon Nitride (BCN) is a complex ternary system that has recently attracted great attention due to its ability to be tuned over a range of chemical, optical and electrical properties. In the last decade, BCN structures have been extensively researched for many energy-related applications, from supercapacitors and lithium ion batteries to electrocatalysts and sensors. However, the stoichiometry dependent properties of BCN as well as the difficult-to-control domain distribution of boron, carbon, and nitrogen atoms throughout the planes result in challenges for the fabrication of devices with reproducible performance. This review starts by discussing the fundamental properties of BCN as compared to its parent compounds (hexagonal boron nitride and graphene). Then the fabrication methods are comprehensively reviewed, analyzing each method's advantages and shortcomings. This is followed by an explanation of BCN characteristics while particular attention is given to the surface chemistry and engineering of nanosheets. Applications of two dimensional BCN will also be reviewed to illustrate its significance over the last decade. Lastly, future trends and prospects of BCN structures will be reviewed, indicating on-going areas of research and the possible integration of BCN in semiconductor and energy-related applications.